Post-COVID19 Lung Fibrosis: An Worrying Experience of COVID19 Survivors (Bangladesh Journal of Medicine, 2021)
Patients recovering from confirmed COVID19 particularly moderate to severe disease, those treated in HDU / ICU support with high flow nasal cannula & Mechanical ventilation ,experienced different symptoms ranging from tiredness, fatigue to severe exertional dyspnea. High resolution CT scan of Chest of these such patients showed persistent radiological abnormalities simulating progressive fibrotic lung disease. Lung function including CO transfer factor revealed moderate to severe reduction. In case of patients recovered from moderate to severe COVID19 pneumonia, lung fibrosis is a big problem and it is one of the most worrying long-term complications. Lung fibrosis was documented in previous Severe Acute Respiratory Syndrome & Middle east Respiratory Syndrome pathology, and current observational studies suggests that pulmonary fibrosis could also complicate infection by SARSCOV2. The objective of our study was to set up a criteria of patients who are at risk to develop such serious complication, thus giving a chance for early detection of post-COVID19 lung fibrosis and thus preventing such disabling complication by proper andearly intervention .Bangladesh J Medicine July 2022; 33(1) : 114-119